(untitled) (Universal International Scientific Journal, 2026)
The article examines the pragmatic properties of phrasal verbs in modern English within the context of teaching English as a foreign language. Special attention is paid to the role of context, extralinguistic and sociocultural factors in interpreting the meanings of phrasal verbs and preventing pragmatic failure among language learners. The study also addresses the problem of phrasal verb polysemy and their predominant use in informal spoken discourse, which often causes significant difficulties in the learning process. The article emphasizes the importance of integrating pragmatic and connotative aspects of phrasal verbs into English language teaching methodology.